RELATIONSHIP BETWEEN LEARNING INDEPENDENCE, INTERACTION OF FRIENDS AND ATTENTION OF PARENTS WITH MATHEMATICAL RESULTS OF CLASS VIII STUDENTS IN MUHAMMADIYAH TEMPURAN, MAGELANG DISTRICT - Yulia Savitri; Harina Fitriyani (Universitas Ahmad Dahlan, 2017)
In this research less of the result of the study mathematic of students are thought with many factors such as independent learning, peer interaction and attention from their parents. This study aims to determine whether there is a positive and significant relationship between independent learning, peer interaction, and attention parents with math learning outcomes eighth-grade students of SMP Muhammadiyah Tempuran Magelang in odd semester in academic year 2016/2017. The populations of this study were all students of class VIII consisted of 4 classes with a total of 90 students. Samples were taken using a random sampling technique. The data collection techniques used the non-test technique by a questionnaire and tests. The test research instruments were: validity tests, different power tests, and reliability tests. The test requirements analysis consisted of a normality test, linearity test, and independence test. The data analysis used product moment analysis and multiple linear regression analysis. The results of the study showed that there was a positive and significant correlation between learning independence, peer interaction, and parents’ attention to the math learning outcomes with R2 = 0,26965, Fcountt= 3,19982 while Ftable= 2,98 thus obtained Fcoun Ftable and multiple regression equation and SR = , SR = , SR = and SE = , SE = and SE = .